2011
DOI: 10.1007/s10544-011-9588-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of cell container arrays with overlaid surface topographies

Abstract: This paper presents cell culture substrates in the form of microcontainer arrays with overlaid surface topographies, and a technology for their fabrication. The new fabrication technology is based on microscale thermoforming of thin polymer films whose surfaces are topographically prepatterned on a micro- or nanoscale. For microthermoforming, we apply a new process on the basis of temporary back moulding of polymer films and use the novel concept of a perforated-sheet-like mould. Thermal micro- or nanoimprinti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…With additional flexible solid layers, acting as transfer membrane, it is also possible to form porous substrates that have great advantages in application as cell culturing scaffold [9]. Structures vary from simple line structures with different ratios to complex hexagonal or honeycomb structures [32,49], which can be perfused or super fused by cell culturing media inside of bioreactor systems.…”
Section: Thermoformingmentioning
confidence: 99%
See 2 more Smart Citations
“…With additional flexible solid layers, acting as transfer membrane, it is also possible to form porous substrates that have great advantages in application as cell culturing scaffold [9]. Structures vary from simple line structures with different ratios to complex hexagonal or honeycomb structures [32,49], which can be perfused or super fused by cell culturing media inside of bioreactor systems.…”
Section: Thermoformingmentioning
confidence: 99%
“…Recent publications and patents are showing that thermoforming technology is well suited to create complex, multilayered material systems [49,50,113,114] (Schober, A., Weise, F., Fernekorn, U., Hildmann, C. et al, Verfahren zur Herstellung eines mikrostrukturierten Formkörpers, DE 10 2012DE 10 103 174.6, 2012. One possible way to realize these complex multiscale structures is to thermoform premanufactured submicron and nanostructured foil.…”
Section: Advanced Thermoforming Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of microfeatures within biomaterial devices for the specific control of cell behavior is an emerging area of interest. Many authors have reported work towards the development of artificial stem cells niches [25][26][27][28][29][30] . This group has recently reported the creation of a microfabricated PEGDA fibronectin-biofunctionalized artificial limbus for the delivery of limbal epithelial cells 22 and a methodology for the fabrication of electrospun biodegradable membranes containing microfabricated pockets for the support of limbal epithelial cells 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering (TE) involves porous scaffolds to act as templates and guides for cell proliferation, differentiation and tissue growth in order to regenerate living tissues . The scaffold surface morphology, together with other substrate stimuli, such as material stiffness, elasticity and chemistry, strongly influence the cell‐substrate interaction and cellular response . The influence of micro‐ and nano‐topography (i.e.…”
Section: Introductionmentioning
confidence: 99%